A digital workflow for accurately and rapidly creating an immediate provisional restoration with natural emergence profile using extracted tooth. Issue 5 (3rd December 2021) - Zhu, Jiakang; Xie, Chenyang; Wang, Yingkai; Yu, Haiyang
Abstract: To describe a digital workflow for creating a provisional restoration by using an extracted tooth rapidly, finally fixing the provisional restoration in the targeted position precisely and preserving the natural emergence profile from the time of provisional restoration to final restoration. Clinical considerations: The use of extracted tooth as an immediate provisional restoration is an effective method for preserving the shape of the emergence profile. However, the existing methods for creating a provisional restoration by using natural tooth are time‐consuming and there is no reliable method to precisely attach tooth to temporary abutment. This case demonstrates a new method for using patient's natural tooth as an immediate provisional restoration under a sequence of guides, which significantly reduces the chair‐side time and inconvenience for clinicians and patients. Immediate provisional restoration contributes to preserving the soft tissue architecture after post‐extraction implant placement, especially when using the patient's tooth as a provisional restoration. Digital technology can help to improve the chair‐side clinical efficiency of dentist. Clinical significance: Maintaining the natural soft tissue architecture is a huge challenge in dental implantology. Use of the extracted tooth as a provisional restoration is likely to achieve an optimal outcome. And digital technology is helpful to the efficiency and accuracy of treatment.